Reserva biológica Alberto Manuel Brenes - Figueroa, Heller; Moreira Schenone, Edgardo; Chaves, José Mario ([San Ramón, C.R.] : Unidad de Televisión, Sede de Occidente, 1990)
Narra las características de la Reserva Biológica, ubicada en San Ramón.
Keywords: RESERVA BIOLOGICA ALBERTO MANUEL BRENES (COSTA RICA)